Current use of imaging and electromagnetic source localization procedures in epilepsy surgery centers across Europe. (25th March 2016) - Mouthaan, Brian E.; Rados, Matea; Barsi, Péter; Boon, Paul; Carmichael, David W.; Carrette, Evelien; Craiu, Dana; Cross, J. Helen; Diehl, Beate; Dimova, Petia; Fabo, Daniel; Francione, Stefano; et al.
Summary: Objective: In 2014 the European Union–funded E‐PILEPSY project was launched to improve awareness of, and accessibility to, epilepsy surgery across Europe. We aimed to investigate the current use of neuroimaging, electromagnetic source localization, and imaging postprocessing procedures in participating centers. Methods: A survey on the clinical use of imaging, electromagnetic source localization, and postprocessing methods in epilepsy surgery candidates was distributed among the 25 centers of the consortium. A descriptive analysis was performed, and results were compared to existing guidelines and recommendations. Results: Response rate was 96%. Standard epilepsy magnetic resonance imaging (MRI) protocols are acquired at 3 Tesla by 15 centers and at 1.5 Tesla by 9 centers. Three centers perform 3T MRI only if indicated. Twenty‐six different MRI sequences were reported. Six centers follow all guideline‐recommended MRI sequences with the proposed slice orientation and slice thickness or voxel size. Additional sequences are used by 22 centers. MRI postprocessing methods are used in 16 centers. Interictal positron emission tomography (PET) is available in 22 centers; all using 18F‐fluorodeoxyglucose (FDG). Seventeen centers perform PET postprocessing. Single‐photon emission computed tomography (SPECT) is used by 19 centers, of which 15 perform postprocessing. Four centers perform neither PET nor SPECT in children. Seven centers apply magnetoencephalography (MEG) source localization, and nine apply electroencephalography (EEG) source localization. Fourteen combinations of inverse methods and volume conduction models are used. Significance: We report a large variation in the presurgical diagnostic workup among epilepsy surgery centers across Europe. This diversity underscores the need for high‐quality systematic reviews, evidence‐based recommendations, and harmonization of available diagnostic presurgical methods.